If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 3 = 0 Reorder the terms for easier multiplication: 3x = 0 Solving 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 0 Simplifying x = 0
| 5x+66=10x+11 | | 2(11x+2y+2)+7x+4=180 | | 14b=16b+72 | | X^2+5x+6=10x | | 12x+6=6x+24 | | 44.7-10n= | | -3x-4=11 | | 12x+-19=3x+8 | | 2x-2y=5 | | 1.10=(17+5)c | | 44.7-12n= | | 10n+4.9= | | 12n+4.9= | | 6(p+2)=30 | | 2(x+6)=5(4x-1) | | .5r+18=36 | | 4a+4b+2-2a+5b-1= | | 58-12.3=18.8 | | 3(5h+9)=57 | | -2x-3=-4x+3 | | 5(.75+.25y)-2y=-9 | | 33.6-10n= | | .75p-12=27 | | 3x^2+4=0 | | 12g-6=7g | | 5(x+3)+1=2x+3(5+x) | | 8x-24=-112 | | 6b+1.50=5.40 | | 6c^12=48 | | 6x-66x-121=0 | | 42x^2-69+20=7x^2-8 | | 52-44.7= |